2005
DOI: 10.14236/jhi.v13i3.599
|View full text |Cite
|
Sign up to set email alerts
|

Randomised studies in general practice: how to integrate the electronic patient record

Abstract: The 'randomised database study' strategy was first proposed in 1997, with the aim of combining the generalisability of observational database studies based on electronic patient records (EPRs) with the validity of randomised clinical trials (RCTs). The key feature was to randomly assign treatments and to use routine care data, as available in the observational database, for patient identification and follow-up. To our knowledge, however, the idea of the randomised database study has not been implemented yet.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to implement and evaluate such a tool in a primary care setting in Germany. Worldwide, only few trials have reported the successful implementation of similar electronic tools [14,15]. While the CTA infrastructure helped to correctly identify a large population at risk with a minimal workload for the practice staff, the staff in nearly all practices missed the target to enrol 200 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to implement and evaluate such a tool in a primary care setting in Germany. Worldwide, only few trials have reported the successful implementation of similar electronic tools [14,15]. While the CTA infrastructure helped to correctly identify a large population at risk with a minimal workload for the practice staff, the staff in nearly all practices missed the target to enrol 200 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our system is the first to support the practice staff in both identifying and surveying eligible patients during daily practice while recording pseudonymised data about the target population in order to monitor selection bias. In a study conducted in the Netherlands [14], the research team used an interactive reminder tool similar to the one described here to inform the GP when an eligible patient was selected by EPR and should be asked to participate in the study. However, eligible patients needed to be selected and marked in the EPR prior to study begin.…”
Section: Discussionmentioning
confidence: 99%